Assessing Avifauna at West Nile Virus Surveillance Site - Griffin, Kelsey; Holley, Amber; Youngblood, Sarah (My University, 2020)
West Nile virus (WNV) is an avian pathogen that is transmitted by mosquito vectors to susceptible birds and dead-end hosts such as humans and horses. WNV was first detected in Georgia in 2001 and has become endemic in the state. Surveillance in Lowndes Co., GA has identified foci of virus activity in mosquitoes, but it is not clear how this relates to the avifauna at these locations. Diversity and density of bird populations are being assessed using passive acoustic monitoring devices at 14 locations where long-term vector surveillance has been conducted. Our study is an essential step towards understanding how avian communities predict WNV in mosquito and human populations.